2021
DOI: 10.3390/ijms22042218
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Toxicology of Major Bioactive Substances in Inocybe Mushrooms

Abstract: Mushroom poisoning has always been a threat to human health. There are a large number of reports about ingestion of poisonous mushrooms every year around the world. It attracts the attention of researchers, especially in the aspects of toxin composition, toxic mechanism and toxin application in poisonous mushroom. Inocybe is a large genus of mushrooms and contains toxic substances including muscarine, psilocybin, psilocin, aeruginascin, lectins and baeocystin. In order to prevent and remedy mushroom poisoning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…11). 90,91 Psylocibin ( 54 ) is dephosphorylated by alkaline phosphatases to produce psilocin ( 55 ), the psychotropic principle, which is then converted to the corresponding O -glucuronide, the main urinary metabolite. 92…”
Section: Isolation Structural Diversity and Pharmacological And Biolo...mentioning
confidence: 99%
“…11). 90,91 Psylocibin ( 54 ) is dephosphorylated by alkaline phosphatases to produce psilocin ( 55 ), the psychotropic principle, which is then converted to the corresponding O -glucuronide, the main urinary metabolite. 92…”
Section: Isolation Structural Diversity and Pharmacological And Biolo...mentioning
confidence: 99%
“…The species diversity of Inocybaceae was documented by a series of studies in China (Fan and Bau, 2010 , 2013 , 2014a , b , 2016 , 2017 , 2018 , 2020 ; Bau and Fan, 2018 ; Fan et al, 2018 ; Yu et al, 2020 ; Deng et al, 2021a , b ; Li et al, 2021b ). Inosperma genus only includes a few toxic species, but a high level of muscarine was frequently detected (Kosentka et al, 2013 ; Sailatha et al, 2014 ; Latha et al, 2020 ; Deng et al, 2021a ; Patocka et al, 2021 ) and was reported constantly in mushroom poisoning incidents from tropical Asia (Chandrasekharan et al, 2020 ; Parnmen et al, 2021 ; Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…( Lurie et al 2009 ). Many Inocybaceae species were well known to contain muscarine (Peredy et al 2014; Patocka et al 2021 ), and various methods have been used to detect this toxin in the past years ( Fahrig 1920 ; Eugster 1957 ; Brown et al 1962 ; Robbers 1964; Kosentka et al 2013 ; Latha et al 2020 ). Five Inosperma species were reported as muscarine positive, including I.…”
Section: Discussionmentioning
confidence: 99%
“…For humans, a lethal dose of muscarine is estimated from 40 mg to 495 mg (Pauli et al 2005). Based on the muscarine concentrations of between 0.1% to 0.33% (dry weight) in Inocybaceae spp., a single mushroom can be lethal ( Puschner 2018 ; Patocka et al 2021 ). Consequently, the two new species proposed by the present study were considered to be more dangerous when mistakenly ingested by humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation